NEGATIVE IMPACT OF FOREST DEGRADATION TO HERPETOFAUNA SPECIES RICHNESS IN KERINCISEBLAT NATIONAL PARK, SUMATRA [Dampak Negatif dari Degradasi Hutan Terhadap Kekayaan Jenis Herpetofauna di Taman Nasional Kerinci Seblat, Sumatra] - Kurniati, Hellen (Research Center for Biology-Indonesian Institute of Sciences, 2009)
Habitat loss and fragmentation are among the largest threats to herpetofauna diversity in tropical rain forest areas, including the rain forest in Kerinci Seblat National Park (KSNP). To measure the rate of negative impact to the herpetofauna population,fifteen survey sites with several degree of habitat disturbance were selected. Based on cluster analysis,15 survey sites were grouped into five distinct clusters, included low elevation forest group, high elevation group, swamp group, disturbed forest group and cultivated land group. Calculation of linier regression for four major (low elevation forest group, high elevation group, disturbed forest group and cultivated land group groups) showed that the rate of locally biodiversity losses were high (R2 > 0.7).